Jesus Christ as the son of David in the Gospel of Mark - Botner, Max (Society for New Testament studies monograph series, 2019)
This study contributes to the debate over the function of Davidic sonship in the Gospel of Mark. In contrast to William Wrede's paradigm, Max Botner argues that Mark's position on Jesus's ancestry cannot be assessed properly though isolated study of the name David (or the patronym son of David). Rather, the totality of Markan messiah language is relevant to the question at hand. Justification for this paradigm shift is rooted in observations about the ways in which ancient authors spoke of their messiahs. Botner shows that Mark was participant to a linguistic community whose members shared multiple conventions for stylizing their messiahs, Davidic or otherwise. He then traces how the evangelist narratively constructed his portrait of Christ via creative use of the Jewish scriptures. When the Davidssohnfrage is approached from within this sociolinguistic framework, it becomes clear that Mark's Christ is indeed David's son.